More energy, more costs. Issue 6 (11th May 2021) - Balan, Prakash; Eng, Marvin H.
Key Points: Transseptal access has been widely disseminated with a relatively low complication rate. The VersaCross Transseptal system utilizes radiofrequency energy to facilitate transseptal access enhancing ease and efficiency of procedures. Rising costs of structural heart interventions may impact resource allocation for medical devices.